Increased TNF-α/IFN-γ/IL-2 and Decreased TNF-α/IFN-γ Production by Central Memory T Cells Are Associated with Protective Responses against Bovine Tuberculosis Following BCG Vaccination - Maggioli, Mayara F.; Palmer, Mitchell V.; Thacker, Tyler C.; Vordermeier, Hans Martin; McGill, Jodi L.; Whelan, Adam O.; Larsen, Michelle H.; Jacobs, William R.; Waters, W. Ray (Frontiers in Immunology, 2016)
Central memory T cells (Tcm) and polyfunctional CD4 T cell responses contribute to vaccine-elicited protection with both human and bovine tuberculosis (TB); however, their combined role in protective immunity to TB is unclear. To address this question, we evaluated polyfunctional cytokine responses by CD4 T cell effector / memory populations from bacille Calmette Guerin (BCG) vaccinated and non-vaccinated calves prior to and after aerosol challenge with virulent Mycobacterium bovis. Polyfunctional cytokine expression patterns in the response by Tcm, effector memory, and effector T cell subsets were similar between BCG-vaccinated and M. bovis-infected calves; only differing in magnitude (i.e., infected > vaccinated). BCG vaccination, however, did alter the kinetics of the ensuing response to virulent M. bovis infection. Early after challenge (three weeks post-infection), non-vaccinates had greater antigen-specific IFN-γ/TNF-α and lesser IFN-γ/TNF-α/IL-2 responses by Tcm cells than did vaccinated animals. Importantly, these differences were also associated with mycobacterial burden upon necropsy. Polyfunctional responses to ESAT-6:CFP10 (antigens not synthesized by BCG strains) were detected in memory subsets, as well as in effector cells, as early as three weeks after challenge. These findings suggest that cell fate divergence may occur early after antigen priming in the response to bovine TB and that memory and effector T cells may expand concurrently during the initial phase of the immune response. In summary, robust IFN-γ/TNF-α response by Tcm cells is associated with greater mycobacterial burden while IFN-γ/TNF-α/IL-2 response by Tcm cells are indicative of a protective response to bovine TB.